Assessing consumers' behavior towards food waste in Pahang, Malaysia / Sara Nabila Ismail and Ainnin Sofea Azeman - Ismail, Sara Nabila; Azeman, Ainnin Sofea (Universiti Teknologi MARA, Perlis, 2021)
Food waste refers to food spoilage and losses that happen in the process the of food supply chain. The occurrence of waste could happen intentionally or accidentally, and towards the end, it can impact others. In this situation, consumer behaviour plays an important role in food waste management. By identifying types of behaviour that influence food waste behaviour to improve consumer behaviour, it can lead to success in waste management. This research used the quantitative approach to measure consumers behaviour in Kuantan and self-administered surveys were used to collect data. The survey was distributed in Kuantan's main areas such as shopping malls, tourist attractions and higher educational institutions. Online platforms were also used to collect data via Google Form on Facebook, Instagram and WhatsApp. Data analysis was conducted to solve the research objectives, questions, and to examine the hypotheses. The data was analysed by using SPSS (version 20). All the questionnaires were returned and the data was then successfully collected and gathered. In total, 98 respondents responded via Google form and 302 respondents responded via hard copy in Kuantan. Based on the result, it shows that the subjective norm and attitude are not predictors of consumer food waste behaviour whereas perceived behavioural control displays a significant relationship with the dependent variables. Additionally, this study is limited to research that is dependent on self-reported data in Kuantan only. Further research on actual food waste by consumers, and how to prevent and reduce food waste in Malaysia is necessary to minimize waste that is sent to landfills. Hence, this study concludes that food waste is a major problem in Malaysia that ends up in landfills as food is not recycled properly.